LEGAL COMPLIANCE IN THE FOREIGN FRANCHISE SECTOR: EXAMINING THE ALIGNMENT BETWEEN FRANCHISE AGREEMENTS AND BUSINESS LICENSING IN INDONESIA - Nugraha, Muhammad Al Haadi; Fathni, Indriya; Kurniawan, Ridha; Damanik, Herlina; Irawan, Agus (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
This study analyzes the legal implications of regulatory disharmony between Government Regulation No. 35/2024 on Franchises and Government Regulation No. 28/2025 on Risk-Based Business Licensing, focusing on the position of the Franchise Registration Certificate (STPW) within the Online Single Submission (OSS) system. Using a normative juridical method with statutory, conceptual, and comparative approaches, the research relies on secondary legal materials legislation, scholarly works, and prior studies examined qualitatively through legal certainty theories and relevant doctrines. Findings indicate three main issues. First, overlapping requirements between STPW and OSS create administrative duplication and potential dual-track enforcement, resulting in legal uncertainty. Second, conflicts arise between public law obligations and private contractual practices in foreign franchise agreements, particularly regarding exclusive supply clauses that contradict local content and MSME partnership requirements. Third, comparative analysis shows that Malaysia’s Franchise Act 1998, strengthened by the 2020 amendment, ensures stronger legal certainty through ex-ante registration, clear deadlines, and enforceable criminal sanctions, providing more credible deterrence than Indonesia’s framework. The study concludes that Indonesia’s franchise regulation remains fragmented and lacks binding statutory authority, which undermines investor confidence and domestic economic protection. It recommends the enactment of a comprehensive franchise law at the statutory level, full integration of STPW within the OSS system, and reinforced sanction mechanisms to enhance legal certainty and create a more conducive business climate.